2018
DOI: 10.1016/j.gaitpost.2018.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Joint moment strategies during stair descent in patients with peripheral arterial disease and intermittent claudication

Abstract: A novel hip extensor strategy was identified in a sub-group of claudicants which acts to reduce the demand on the knee extensors, but not the plantarflexors. Weakness in the knee extensors may prevent redistribution of the task demand, typically seen in older adults in stair descent, away from the functionally limited plantarflexor muscle group. Further investigation into multi-level joint strength and the relationship to functional tasks is warranted to inform targeted intervention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Raw marker coordinate data was interpolated and filtered using a zero-lag fourth order low-pass Butterworth filter with a cut-off frequency of 6 Hz [24]. Kinetic data was subject to a low pass filter with a cut-off frequency of 15 Hz [27]. Kinematic and kinetic data were computed, cropped and normalised to 100% gait cycle with 0% indicating initial foot contact [7].…”
Section: Discussionmentioning
confidence: 99%
“…Raw marker coordinate data was interpolated and filtered using a zero-lag fourth order low-pass Butterworth filter with a cut-off frequency of 6 Hz [24]. Kinetic data was subject to a low pass filter with a cut-off frequency of 15 Hz [27]. Kinematic and kinetic data were computed, cropped and normalised to 100% gait cycle with 0% indicating initial foot contact [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of stair ascent and descent in patients with PAD 42,43 reported a statistically significant reduction in the vertical and propulsion forces during stair climbing in patients with PAD compared to controls. The severity of PAD was also correlated with increased peak medial forces and reduced peak propulsion forces during stair ascent.…”
Section: Ground Reaction Forcesmentioning
confidence: 99%
“…Consequently, a tailor-made and well-assigned handrail systems along the circulation route within the public domain with respect to the elderly is necessary in an age-friendly community [5]. Handrails are necessary in an age-friendly community, as they solve problems associated with the elderly, such as common diseases, including osteoporosis, and disabilities [1]. Sometimes, handrails can act as a gadget for the elderly when intense physical effort is required.…”
Section: Of 32mentioning
confidence: 99%
“…Nevertheless, a fast-changing environment results in a gradually departure from the original picture of a city of elderly. To understand and get used to the environment, regulations, guides, or codes should be amended and improved according to physical characteristics and needs of the older generation around the world; otherwise, geniality would be lost along the way [1].…”
Section: Introductionmentioning
confidence: 99%